Evaluating generator damping for wind‐integrated power system in ambient conditions. Issue 2 (29th October 2021) - Sun, Zhenglong; Liu, Chunli; Jiang, Quanfeng; Levron, Yoash; Cai, Guowei
Abstract: This paper proposes a power system multimode generator energy loss factor (GELF) based on energy flow method under environmental excitation. This index can evaluate generator damping changes in different oscillation modes in power systems, timely discover the damping deterioration of the generator, and track the source of low‐frequency oscillation. A signal expression method for electrical frequency domain under environmental excitation is derived. This method is combined with dissipated energy flow method to obtain a new type of GELF. In terms of signal processing, dynamic mode decomposition and Morlet wavelet filter extraction system mode components are used to improve computing accuracy. The proposed index enables online calculation with the support of phasor measurement unit and wide area measurement system. Simulation analysis is conducted in a standard 39 node system and wind‐integrated power system. Test results show the effectiveness and generality of the proposed index and method.